2020
DOI: 10.3390/su12041571
|View full text |Cite
|
Sign up to set email alerts
|

Can Stock Investor Sentiment Be Contagious in China?

Abstract: This paper explores the impact of investor sentiment on financial markets in China by taking the quantile causality test. We find that government bond markets, gold markets, and foreign exchange markets are affected by stock investor sentiment, except for in the corporate bond market. In extreme situations, such as excessively optimistic or pessimistic sentiment, these markets will become more vulnerable to suffering from drastic fluctuations. On the contrary, the market return in government bonds, corporate b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 105 publications
1
7
0
Order By: Relevance
“…observed that disseminated information has a different impact on informed and uninformed traders. According toHe et al (2020), investor sentiments have an asymmetrical relationship with stock return as well as stock volatility Su et al (2020),Anusakumar et al (2017)Verma and Verma (2007); andGong et al (2022) also confirmed the Noise trading model by highlighting the fact that investor sentiments positively affect market returns.…”
mentioning
confidence: 57%
“…observed that disseminated information has a different impact on informed and uninformed traders. According toHe et al (2020), investor sentiments have an asymmetrical relationship with stock return as well as stock volatility Su et al (2020),Anusakumar et al (2017)Verma and Verma (2007); andGong et al (2022) also confirmed the Noise trading model by highlighting the fact that investor sentiments positively affect market returns.…”
mentioning
confidence: 57%
“…Furthermore, though liquidity was important for the stability of financial markets and the growth of national economies, the liquidity of financial markets might be influenced by country risk shocks through informational asymmetry, funding constraints, and portfolio rebalancing activities (Kunjal 2022). Especially, exploring the impact of investor sentiment on financial markets in China by taking the quantile causality test, Su et al (2020) claimed that the authorities could sustain the stabilization of financial markets by reducing information asymmetry, guiding the rational sentiment of investors, and increasing effective regulations.…”
Section: Literature Review Information Asymmetrymentioning
confidence: 99%
“…As the investor sentiment became popular among practitioners, some papers investigate the contagious effect of sentiment on different markets, such as gold, bond and foreign exchange markets. For example, Su et al (2020) using the quantile causality test, explore the effects of investor sentiment on government, corporate bond markets, gold and foreign exchange markets. Monthly data covers the period from July 2005 to April 2019 and the results show a positive effect of investor sentiment on government bond markets, gold and foreign exchange markets; while there is no relationship between investor sentiment and corporate bond markets.…”
Section: Related Research Overviewmentioning
confidence: 99%